How professional learning communities create and sustain teacher change in practice - A grounded theory study of conditions and context - McDonald, Barbara Lee Schartz (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2020)
This United States-based study uses a grounded theory approach to develop a theoretical understanding of change in teacher practice. This change in practice is mediated through a specific type of community of practice developed using Professional Learning Community goals and activities. Traditionally, professional change was driven by deficit-focused professional development events delivered out of context. Current research on teaching-based professional development is coming to the conclusion that context, collaboration, and immersion are critical elements of effective professional development. Even with the inclusion of these elements, traditional professional development methods are not succeeding at creating the change that is needed. There currently exists a situated learning model of professional development that has quantified its ability to improve student outcomes: a Professional Learning Community (PLC). In Professional Learning Communities the context of the school district and school determine what needs to be learned. Collaboration within the community drives teacher immersion into student learning. While there is excellent research around the organizational development aspects that create a PLC, there is little-to-no research on the context and conditions that change teacher practice. PLC design is based on organizational change and organizational learning theory. There is little reference, in the key PLC literature, to communities of practice theory. However, the analysis in this study demonstrates that successful PLCs become a specific type of community of practice. It is important to recognize the structure and impact of communities of practice theory in PLCs in order to understand how the organizational development and learning activities of PLCs create learning and change in teacher practice. The purpose of this study is to develop a theoretical understanding of the context and conditions within PLCs that create and sustain change in teacher practice. The need to develop theoretical understanding of the changes in teacher practice that occur during the organizational development of the PLC drove the selection of grounded theory as the research methodology. The study included PLCs from a primary school district as well as one school PLC that had documented success in improving student performance. Additionally, the researcher sought out non-technical literature on related concepts. Data was primarily collected through 15 semi-structured interviews, observations, and non-technical literature. Theoretical sampling between multiple PLCs, observations, and non-technical literature drove the data collection. Concurrent to data collection, constant comparison of the data was achieved through open, axial, and selective coding. These activities allowed the researcher to move from conceptualization of the data to an emerging, substantive, mid-range theory with explanatory and predictive power. The main contribution of this research study is a substantive, mid-range theory that explains how effective PLCs form and create teacher change in practice that improves student performance. This change is demonstrated through a three-phase model that explains the process and structure of the change in teacher practice as well as uses communities of practice theory to explain the conditions and context for teacher learning that changes practice. The significance of this study are 1) it provides conditions and context for creating and sustaining teacher change through PLCs; 2) it extends the existing literature by adding the lens of community of practice theory to explain how and where learning happens.
APPROVED
Keywords: Professional learning; CPD; Professional learning communities; PLC; Teacher professional learning; Grounded theory